2013
DOI: 10.1007/s00330-013-2985-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced and ultra-high-resolution breast MRI at 7.0 Tesla

Abstract: • Magnetic resonance imaging is important in the evaluation of breast cancer. • Recently, 7-T MRI has become available. • The 7-T dynamic contrast-enhanced breast MRI is feasible in patients. • The 7-T breast examinations are amenable to evaluation according to BI-RADS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Additionally, studies indicate that in women recently diagnosed with unilateral breast cancer, additional cancer lesions are sometimes detected in the contralateral breast [25]. Several 7T breast studies have indicated a need for bilateral coil design [8], [11]. On the other hand, in some applications, e.g., proton decoupling in second-nuclei applications, a unilateral coil may be preferred, since it enables judicious use of the available total proton decoupling power in a single breast [26]–[28].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies indicate that in women recently diagnosed with unilateral breast cancer, additional cancer lesions are sometimes detected in the contralateral breast [25]. Several 7T breast studies have indicated a need for bilateral coil design [8], [11]. On the other hand, in some applications, e.g., proton decoupling in second-nuclei applications, a unilateral coil may be preferred, since it enables judicious use of the available total proton decoupling power in a single breast [26]–[28].…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node spiculation, typically evaluated in histology, is linked to malignancy and as an indication of extranodal extension, linked to aggressive tumor types with poor prognosis . Wendl et al reported on 3T DCE of lymph nodes in the neck; with 1 × 1 × 2 mm voxels, the authors note that partial volume effects degrade the ability to reliably differentiate malignant from benign lymph nodes with <10 mm diameter, and SNR limits the ability to improve spatial resolution. We demonstrate that our coil is capable of resolving lymph nodes with 3‐mm cross‐sections.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of performing MR at ultrahigh field strengths include a higher SNR and a higher chemical shift . The first advantage can be used to increase spatial resolution, which has been shown to be feasible in a clinical setting and might have potential for earlier and better diagnosis . Additionally, a better spatial resolution enables the assessment of tumor heterogeneity .…”
Section: Introductionmentioning
confidence: 99%